The study of factors affecting the quality of pharmaceutical specialists training - Ткаченко, Наталя Олександрівна; Громовик, Богдан Петрович (ScienceRise: Pharmaceutical Science, 2016)
Aim. The study of factors affecting the quality of pharmaceutical specialists training for the further possibility of inertia leveling of reforms in higher pharmaceutical education development, as well as improving the efficiency of its control. Results. Expert assessment of the impact factors influencing, according to many scientists and practitioners, on quality of pharmaceutical graduates training was carried out. Pharmacy specialists from 11 regions of Ukraine were experts. Two groups of factors according the influence vector on the quality of the educational process were formed: 1 – positive impact (27 factors), 2 - negative impact (15 factors). Among the positive factors, “attracting highly qualified specialists of practical pharmacy in the educational process” and “improve the quality of practical and theoretical training of pharmaceutical specialists using innovative technologies” had leading positions. “Corruption in system of education and commercialization of the educational process” was the most relevant negative factor. Conclusion. Positive and negative impact factors influencing on the quality of education and forming the competitiveness of pharmaceutical graduates was determined. The necessity of development of new motivational instruments for practical pharmacy for the active engagement of the private pharmaceutical business in the process of young specialists training was substantiated. The obtained data can be used to elaborate the strategy for the further reform in the system of pharmaceutical education and development of peculiar strategic and tactical plans of universities